The "Four Word Decision" of Improving Quality and Efficiency in Primary School Mathematics Classroom Teaching - Niu, Xuexing (Journal of Theory and Practice of Contemporary Education, 2023)
Dewey, a famous American educator, pointed out that "teaching is not a simple telling. Teaching should be a process experience, an experience, and an understanding." How to make students like to learn, learn and learn mathematical knowledge in mathematics class, form mathematical application ability, and then experience the charm of mathematical thinking, and complete the extension from mathematics class to life is a problem I have been concerned about and thinking about. Through learning and practice, I believe that in mathematics teaching, we should focus on "refinement", "living", "change", and strive for "reality", and read "four word decision" well, so as to promote more effective and efficient mathematics classroom practice activities.